Response Of Bacillus Subtilis In Clonalcolony Competition - Law, Heng Chuan (2022)
Competition is a common occurring in the natural environment due to the limitation of resources and spaces. Long term competition will eventually lead to stable coexistence. This research aims to investigate and establish the effect of clonal colony competition in Bacillus subtilis. This includes the physiological condition, viability status and transcriptomic response of the cell. When B. subtilis colonies are grown close together, growth occurs to a certain size with a distinct front, leaving a gap between them. Growth appeared to be arrested on the fronting side, while the side that did not face any other colony continued to grow outward and extend the morphology of the colony. Based on viability staining. the majority of the cells on the fronting sides of a 72-hour colony were either dead or undergoing changes to their cell membranes. Bacterial cells from the fronting side were observed to be sporulating by light microscopy, while cells on the outward growing side were unaffected. Transmission electron microscopy revealed that the cells on the fronting sides were mostly endospores, while the cells on the outward growing sides were mostly actively dividing vegetative cells with elongated nucleoplasmic body. A comparative transcriptomic analysis showed that the majority of the up-regulated genes in the cells on the front side are related to oxidative and nutrient stress. These distinct and highly up-regulated adaptive responses indicated that the cells were subjected to a variety of stress.